Influence of Intellectual Capital, Intangible Assets, Public Ownership, and Institutional Ownership on Financial Distress - Kania Vera Ayu; Richad Wahyu Pratama; Ngoan Quynh Thi Nguyen (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to provide empirical evidence on the effect of Intellectual Capital, Intangible Assets, Public Ownership, and Institutional Ownership on Financial Distress in primary consumer sector companies listed on the Indonesia Stock Exchange. Design/methodology/approach – This study employs a quantitative research approach using secondary data from 48 primary consumer sector companies listed on the Indonesia Stock Exchange during the period 2021–2024. Financial Distress is measured using the Altman Z-Score (1995) model for non-manufacturing and emerging market firms. Hypothesis testing is conducted using logistic regression analysis with EViews 9 software. Findings – The results indicate that Intellectual Capital has a negative and statistically significant effect on Financial Distress. Intangible Assets have a positive but statistically insignificant effect on Financial Distress. Furthermore, Public Ownership has a negative and statistically significant effect on Financial Distress. Meanwhile, Institutional Ownership has a positive but statistically insignificant effect on Financial Distress. Research limitations/implications – This study is limited to the 2021–2024 period, during which incomplete financial disclosures and firm losses reduced the sample size. The findings provide practical implications for corporate managers to prioritize effective intellectual capital management and ownership structures that enhance monitoring quality. For investors and regulators, the results suggest that not all governance mechanisms—particularly institutional ownership—function effectively in reducing financial distress within the primary consumer sector, highlighting the need for improved governance practices and transparency. JEL : G32, G33, M41